Concilio Newscarta, 1978 - Concilio::::::::::::::: (2024)
Friday, April 21, 1978. Volume I, Number 1. A newsletter published quarterly, focusing on Chicano-related issues. This first issue describes the Concilio at San Jose State University, an initiative to unite Chicano student organizations into a coalition. The Concilio, functioning as an umbrella organization, aimed to unify and guide these groups.